Factors associated with small airway obstruction in COVID-19 survivors: A cross-sectional study among health-care providers - Aritonang, Minarni ES.; Pandia, Pandiaman; Pradana, Andika; Ashar, Taufik (Narra J, 2023)
Coronavirus disease 2019 (COVID-19) has been identified for more than two years, yet studies assessing post-infection lung function are limited. Reports on lung function in COVID-19 patients indicate that patients have restrictive defects and small airway dysfunction that can persist and are not necessarily related to the severity of the disease. The aim of this study was to assess the incidence of small airway obstruction and its incidence-associated factors among COVID-19 survivors to better describe the long-term effects of COVID-19. A cross-sectional study was conducted among COVID-19 survivors who less than 50 years at Medan Adventist Hospital between 2020–2022. The data were collected through interview, direct assessment and respiratory examination. A total of 89 COVID-19 survivors were recruited of which the majority of them were female with a mean age of 32.6-year-old with the largest group was 19–30 years. The comorbidities found among the survivors were heart and thyroid disorders, with the most common symptom of post-COVID-19 was fatigue. Most of them had mild COVID-19. The mean forced mid-expiratory flow (FEF25–75%) was 96.3±20.22, with an incidence rate of small airway obstruction was 19.1%. Univariate and multivariate analyses indicated no significant association between age, gender, comorbidities, history of oxygenation during COVID-19 treatment, COVID-19 severity and the type of post COVID-19 syndrome symptoms with the incidence of small airway obstruction. In conclusion, among COVID-19 survivors who were less than 50 years old, those studied variables seems have less association with the incidence of small airway obstruction. Nevertheless, a further study with a bigger sample size is important to be conducted.